Insight into IELTS : - Jakeman, Vanessa. (NXB Đà Nẵng, 2004)
This book consists of four parts: Listening, Reading, Writing and Speaking sections; Supplementary activities for each unit; A complete practice test; and Recording Script and Answer Key.